(untitled) (Research, Society and Development, 2021)
Entrepreneurship in Nursing represents the search for unexplored activities, better remuneration and strategic articulation for solving problems related to the profession. The study aimed to describe how business entrepreneurship has been outlined in nursing and what are the possibilities for entrepreneurial performance of nurses. This is an integrative literature review study with a qualitative approach. The inclusion criteria were defined as: primary articles, published in full, in Portuguese, in the period from 2011 to 2021; as exclusion criteria: articles that did not refer to the Brazilian context and the proposed object and theoretical review studies. Data collection was carried out in the databases: Virtual Health Library (VHL), Latin American and Caribbean Health Literature (LILACS), Scientific Electronic Library Online (SciELO). The study consisted of eight articles with an evidence level of 4 studies. The results were presented from two thematic categories: The profile of business entrepreneurship in Brazil and Characteristics of the entrepreneur nurse in Brazil. It is observed that the profile of business entrepreneurship in Brazilian nursing is concentrated in large capitals, registered as a nursing activity and that these entrepreneur nurses are predominantly female, aged between 26 and 56 years, with some specialization. It is concluded that there is a gap in relation to the knowledge of business entrepreneurship in Brazilian nursing, being it is necessary to increase studies that demonstrate the successful experiences of nurses in the area.